Mixed Convection Of A Hybrid Nanofluid Flow Along A Vertical Surface Embedded In A Porous Medium - Pop, Ioan; Waini, Iskandar; Ishak, Anuar; Groşan, Teodor (Elsevier Ltd, 2020)
The steady mixed convection flow along a vertical surface embedded in a porous medium with hybrid nanoparticles are examined. Both assisting and opposing flows are considered. We consider alumina (Al2O3) and copper (Cu) as the hybrid nanoparticles which are suspended in water to form Al2O3-Cu/water hybrid nanofluid. The similarity equations are gained from the governing equations using the similarity variables, and their solutions are obtained by the aid of the bvp4c solver in Matlab software. We found that there exist dual solutions for the case of opposing flow. Besides, it is noticed that the added hybrid nanoparticles delay the separation of the boundary layer. In addition, the velocity of the hybrid nanofluid is increased for the upper branch solutions, but the observation is reversed for the lower branch solutions as Cu nanoparticle increases.